Macroscopic Visualization: Macroscopic Visualization of Fast Electrochemical Reaction of SrCoOx Oxygen Sponge (Adv. Mater. Interfaces 23/2019). Issue 23 (6th December 2019) - Yang, Qian; Cho, Hai Jun; Jeen, Hyoungjeen; Ohta, Hiromichi
Abstract : In article number 1901260, Hyoungjeen Jeen, Hiromichi Ohta, and co‐workers visualize the fast topotactic electrochemical oxidation reaction of SrCoO x oxygen sponge. The columnar oxidation from insulating SrCoO2.5 to metallic SrCoO3−δ occurs along the surface normal direction and then spread in the perpendicular to the normal direction.